Uma costura de tempo: memória e utopia na poesia de Manuel Bandeira - Nascimento, Patrício Alves do (2008)
The purpose of that dissertation is to analyze as they are configured, in Manuel Bandeira's poetry, themes as the memory and the Utopia. For so much, the poems were selected Vou-me embora pra Pasárgada and Teresa, texts that are shown open to the analysis of those themes. In our analysis, we began by thinking what is the poetic and what characterizes it. We saw that it is born with the mythical thought and it is a type of permanence of the main characteristics of this thought: amalgam between the memory and the search of a truth or answer for the being. We related that subject of the search with the perception of the lack in the poetic bandeiriana; it lacks of a body and of a future, that is reflected in the construction of his poetry, deeply linked to the themes of the finiteness and of the memory. Starting from philosopher Henri Bérgson's theories and of novelist Marcel Proust, we passed to the analysis of the theme of the memory, defending it, in the poetry bandeiriana, as recovery possibility and of recriação of what it was. Like this, we noticed that the theme of the memory was directly linked to the theme of the Utopia, because in a poem as Vou-me embora pra Pasárgada, the recovery of an individual past goes directly by the tradition of a promised land to all, mythical, true. In Teresa, it happens the inverse process: of the collective memory, through the literary rereading, we pass to the individual longing of communion with the other, through the love. We concluded that the poetry banderiana is a rereading process and permanent recreation, a pendulum that keep going from one to the other to return full of new meaning for the first one. The poetry as a process of seam of a particular person, that borns starting from itself and that necessarily goes by the other